Targeting Cytokine Storm in COVID-19: A Role of Online Hemodiafiltration with Asymmetric Cellulose Triacetate in Maintenance Hemodialysis Patients—A Report of 10 Cases. (15th March 2021) - De La Flor, José C.; Valga, Francisco; Marschall, Alexander; Monzon, Tania; Albarracín, Cristina; Ruiz, Elisa; Rodeles, Miguel
Abstract : Early reports have suggested that maintenance hemodialysis (MHD) patients could be more susceptible to a severe course of COVID-19. Among the therapeutic approaches, the use of drugs that reduce the cytokine storm characteristic of this disease has been proposed. Some dialyzers, such as the new generation of asymmetric cellulose triacetate (ATA) membranes, could favor the effective elimination of medium-sized molecules and other inflammatory mediators. In this case series, we describe in depth the clinical, analytical, and radiological details, therapeutic aspects, and outcomes of the case series of 10 MHD patients of our dialysis unit, who tested positive for SARS-CoV-2 from 5 October to 30 November 2020. Furthermore, we evaluate the removal of hyperinflammatory parameters with the ATA membrane in postdilution online hemodiafiltration (OL-HDF) in these patients through a variety of biomarkers of systemic inflammation from the diagnosis until stripping. Biochemical blood analysis was carried out at baseline and at days 7 and 14 after diagnosis, respectively. 50% of the patients presented COVID-19 pneumonia and required hospital admission. Median hospitalization time was 21 days. A total of 4 patients developed severe pneumonia (3 of them died) and 1 patient developed moderate pneumonia. Patients who died ( n = 3) were more likely to present bilateral pneumonia (100% vs 14.3%) at diagnosis and less reduction in interleukin 6 (IL-6) at day 14, as compared to those who survived. The use of the ATA membrane could be considered a therapeutic option, due to its immunomodulatory effect in MHD patients with SARS-CoV-2 infection, especially at the beginning of the disease, where the inflammatory component is predominant.